Methodology for the rapid force of baseball bats in the province of granma, participants in national series (Original) (Revista científica Olimpia, 2019)
Proper strength training in baseball hitters is a key to their competitive performance aspect; This is pretended to be solved with the following objective: To develop a methodology supported by the implementation of the Optimal Zone training system, in its current zone 3, which allows rapid increase in strength and its maintenance during the competition in baseball hitters who are partakers in national series. It is elaborated the theoretical concept underlying the proposed methodology, which is assessed by the expert judgment and conducting an experiment in the 49th national series and its replication in 50th, specifically in periods of direct training to competition (PDC), in which the significant increase of the rates of rapid force in the baseball.
Keywords: rapid force; optimal zone training system; zone 3